2020
DOI: 10.3892/mmr.2020.11631
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the mechanisms underlying the protective effect of tetramethylpyrazine against cisplatin‑induced in vitro ototoxicity in HEI‑OC1 auditory cells using gene expression profiling

Abstract: Sensorineural hearing loss is prevalent in patients receiving cisplatin therapy. Tetramethylpyrazine (Tet) and tanshinone iia (Tan iia) have protective roles against hearing impairment or ototoxicity. The present study aimed to investigate the molecular mechanisms underlying cisplatin-induced ototoxicity and the protective effect of Tet and Tan iia against it. House ear institute-organ of corti 1 auditory cells were treated with titrating doses of Tan iia, Tet, and cisplatin. in a cell viability assay, cisplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Among the commonly decreased mRNAs, Cdkn1a, Egr1, and Ctgf are notable hub genes. A study about cisplatin-induced ototoxicity in auditory cells indicated that Cdkn1a (p21) may be involved in hearing impairment or ototoxicity (28). Moreover, the histone deacetylase inhibition can protect hearing against acute ototoxicity; meanwhile, after treatment, the pro-survival gene Cdkn1a (p21) was elevated (29).…”
Section: Discussionmentioning
confidence: 99%
“…Among the commonly decreased mRNAs, Cdkn1a, Egr1, and Ctgf are notable hub genes. A study about cisplatin-induced ototoxicity in auditory cells indicated that Cdkn1a (p21) may be involved in hearing impairment or ototoxicity (28). Moreover, the histone deacetylase inhibition can protect hearing against acute ototoxicity; meanwhile, after treatment, the pro-survival gene Cdkn1a (p21) was elevated (29).…”
Section: Discussionmentioning
confidence: 99%
“…The gDNA was harvested by eluting in 100 μl buffer EB while purity was evaluated using the NanoDrop (Thermo Fisher, United States) and gel electrophoresis using 1% agarose. Quantification of gDNA was carried out using the Qubit double-stranded DNA high-CHS kit following the manufacturer’s guidelines (Life Technologies Inc., Carlsbad, CA, United States) ( Guan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The purity of gDNA was assessed using the NanoDrop (Thermo Fisher, Arbor, Michigan United States) and gel electrophoresis using 1% agarose. Quantification of gDNA was done using the Qubit double-stranded DNA high-CHS kit based on the manufacturer’s instructions (Life Technologies Inc., Carlsbad, CA, United States) ( Guan et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%